2011
DOI: 10.1002/maco.201006046
|View full text |Cite
|
Sign up to set email alerts
|

A new steel with good low‐temperature sulfuric acid dew point corrosion resistance

Abstract: In this work, new steels (1#, 2#, and 3#) were developed for low‐temperature sulfuric acid dew point corrosion. The mass loss rate, macro‐ and micro‐morphologies and compositions of corrosion products of new steels in 10, 30, and 50% H2SO4 solutions at its corresponding dew points were investigated by immersion test, scanning electron microscopy (SEM) and energy‐dispersive spectrometry (EDS). The results indicated that mass loss rate of all the tested steels first strongly increased and then decreased as H2SO4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
12
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 16 publications
0
12
0
Order By: Relevance
“…However, the problem of dew point corrosion and coupling effect with viscous ash deposits arises with a decrease in gas temperature, and this would affect the long‐term safe service of the flue gas deep cooling device in power plants. Previous studies focused on sulfuric acid dew point corrosion rate and wall temperature , there were also studies on low‐temperature sulfuric acid dew point corrosion resistance of steel . In fact, our experimental result showed that the main problem is the coupling mechanism between dew point corrosion and viscous ash deposits, but few researchers did such studies owing to its complexity .…”
Section: Introductionmentioning
confidence: 84%
“…However, the problem of dew point corrosion and coupling effect with viscous ash deposits arises with a decrease in gas temperature, and this would affect the long‐term safe service of the flue gas deep cooling device in power plants. Previous studies focused on sulfuric acid dew point corrosion rate and wall temperature , there were also studies on low‐temperature sulfuric acid dew point corrosion resistance of steel . In fact, our experimental result showed that the main problem is the coupling mechanism between dew point corrosion and viscous ash deposits, but few researchers did such studies owing to its complexity .…”
Section: Introductionmentioning
confidence: 84%
“…In various corrosive environments such as atmospheric corrosion, H 2 S/CO 2 gas corrosion and sulfuric acid dew point corrosion, the fineness of the rust particles is an important factor for the protective rust layer . Ishikawa et al reported that the specific surface area of rust particles formed by the exposure of various types of steel to various environments decreased with an increase in airborne salinity and the corrosion rate, which indicated that the rust particles grow as corrosion progresses, and the resultant rust layer becomes less compact and its protective properties decrease.…”
Section: Introductionmentioning
confidence: 99%
“…Sulfuric acid dew point corrosion occurs in sectors in flue gas treatment systems, such as gas‐gas heat exchangers (GGH for short), flue and chimney in electric power, metallurgy, and petrochemical industries . Generally, protection of GGH is mainly divided into two categories: (i) Using corrosion resistant steel, such as ND (09CrCuSb), S‐TEN (12CuSb), TAICOR‐S (12CrCuAl) and CRIA (10CrCu); (ii) Employing low carbon steel with a protective coating, in which enamel coating attracts much attention.…”
Section: Introductionmentioning
confidence: 99%